Bitter-tasting drugs tune GDF15 and GLP-1 expression via bitter taste or motilin receptors in the intestine of patients with obesity - Qian Wang; Mona Farhadipour; Theo Thijs; Emily Ruilova Sosoranga; Bart Van der Schueren; Laurens J. Ceulemans; Ellen Deleus; Matthias Lannoo; Jan Tack; Inge Depoortere (Elsevier, 2024)
Objective: Growth differentiation factor 15 (GDF15), a stress related cytokine, was recently identified as a novel satiety signal acting via the GFRAL receptor located in the hindbrain. Bitter compounds are known to induce satiety via the release of glucagon-like peptide 1 (GLP-1) through activation of bitter taste receptors (TAS2Rs, 25 subtypes) on enteroendocrine cells in the gut. This study aimed to investigate whether and how bitter compounds induce a stress response in intestinal epithelial cells to affect GDF15 expression in patients with obesity, thereby facilitating satiety signaling from the gut. Methods: The acute effect of oral intake of the bitter-containing medication Plaquenil (hydroxychloroquine sulfate) on plasma GDF15 levels was evaluated in a placebo-controlled, double-blind, randomized, two-visit crossover study in healthy volunteers. Primary crypts isolated from the jejunal mucosa from patients with obesity were stimulated with vehicle or bitter compounds, and the effect on GDF15 expression was evaluated using RT-qPCR or ELISA. Immunofluorescence colocalization studies were performed between GDF15, epithelial cell type markers and TAS2Rs. The role of TAS2Rs was tested by 1) pretreatment with a TAS2R antagonist, GIV3727; 2) determining TAS2R4/43 polymorphisms that affect taste sensitivity to TAS2R4/43 agonists. Results: Acute intake of hydroxychloroquine sulfate increased GDF15 plasma levels, which correlated with reduced hunger scores and plasma ghrelin levels in healthy volunteers. This effect was mimicked in primary jejunal cultures from patients with obesity. GDF15 was expressed in enteroendocrine and goblet cells with higher expression levels in patients with obesity. Various bitter-tasting compounds (medicinal, plant extracts, bacterial) either increased or decreased GDF15 expression, with some also affecting GLP-1. The effect was mediated by specific intestinal TAS2R subtypes and the unfolded protein response pathway. The bitter-induced effect on GDF15/GLP-1 expression was influenced by the existence of TAS2R4 amino acid polymorphisms and TAS2R43 deletion polymorphisms that may predict patient's therapeutic responsiveness. However, the effect of the bitter-tasting antibiotic azithromycin on GDF15 release was mediated via the motilin receptor, possibly explaining some of its aversive side effects. Conclusions: Bitter chemosensory and pharmacological receptors regulate the release of GDF15 from human gut epithelial cells and represent potential targets for modulating metabolic disorders or cachexia.